Use of the game-based learning platform KAHOOT! to facilitate learner engagement in Animal Science students - Kristie E. Cameron; Lewis A. Bizo (Association for Learning Technology, 2019)
Gamification of instructional activities is a useful approach that educators can use to promote more effective learning environments by increasing problem-solving, critical thinking and competence in the classroom. 'KAHOOT!' is an online multi-player real-time quiz game that allows students to measure learning in an engaging, immediate and entertaining manner. Lecturers can measure how well students absorb information and tailor their teaching to the next step or re-teach a concept after poor uptake by students. Seventy-two students participated in a 20-question survey about their experiences with 'KAHOOT!'. Engagement scores were correlated with assessment grades to measure if 'KAHOOT!' affected student learning and achievement. The survey was deemed statistically sound in reliability and validity testing, and a principal components analysis (PCA) revealed that the attributes were strongly linked. There was no relationship between engagement score and assessment grade, indicating that 'KAHOOT'!' did not directly increase achievement. However, assessment of individual responses identified that students found it to be a positive social learning technology as it provided a fun, competitive and immersive end to a class. The benefits of fostering engagement, enjoyment and immersion within adult learning are especially important for maintaining a level of achievement within education to ensure that students are better equipped to deal with challenges and can turn a potential failure into an opportunity to improve their scholarship. The challenge provided by this study is to identify now how to measure the value of 'fun' activities in the tertiary classroom as a reinforcer for engagement, participation and learning.